PENETAPAN UKURAN SASARAN SEBAGAI USAHA PENINGKATAN EFISIENSI PROSES PENGGERGA.JIAN DI LIMA KILANG PENGGERGAJIAN - Osly Bachman; Syarlf Hidayat (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
nlri•t a. Is ou of the factors that determine aawin6 efficiency. Tlls objectiue of thit dudy wa to provide the lnfonnatlon on the •wmlllfnl e('ficMney in 80me Indonaian •wmillt. The data for the analy.U were• from 8 •wmilk In Central .llUll and 2 •wmllla In .limbL Ou hundred board• from each •wmlll were randomly tuleen to evaluate the uariition of the tlaiclenna within and betroeen t board•, and to determine the deviation of the board tlaicleu• from the ,.,,., ,,_ in each •wmlll.'f1ae tlaicleJllla between the board• waa fQund to be more •riable compared with the tlaicle,..,, within the board&. EllfJJthoulla tlN laf61aat deviation of the board• found In tlaia atudy wa• llelow PPKGRI atandard, ..,,.ation waa made •lam ro minlmlH tlaiclenaadeviation, and the po•ible lmprouement and maintenance of the aetwork.